PENGARUH CORPORATE SOCIAL RESPONSIBILITY, GREEN ACCOUNTING, KINERJA KEUANGAN DAN STRUKTUR KEPEMILIKAN TERHADAP NILAI PERUSAHAAN (Studi Empiris pada Perusahaan Sektor Energi dan Basic Materials yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Rizky Tsaniyatun Rofi’ah; Darsono Darsono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the influence of Corporate Social Responsibility, Green Accounting, financial performance, and ownership structure on the value of companies in the energy and basic materials sectors. Each independent variable in this study was measured using the GRI Standard 2021 for Corporate Social Responsibility, and the PROPER rating for Green Accounting. Meanwhile, financial performance was measured using Return on Assets (ROA), and ownership structure was measured using institutional ownership. This study focused on companies in the energy and basic materials sectors listed on the Indonesia Stock Exchange for the 2021-2024 period. Data was collected by examining the annual reports of the relevant companies accessed through the company's official website and obtained from Bloomberg FEB Undip. The sample was selected using a purposive sampling technique based on predetermined criteria, resulting in 145 sample companies. The collected data were then analyzed using multiple linear regression. The results of this study found that financial performance had a positive effect on company value in the energy and basic materials sectors, and Green Accounting had a positive effect in a sensitivity test for the basic materials sector. Corporate Social Responsibility and ownership structure were not found to influence company value.